Chaos and complexity in the classical-quantum transition - Kowalski, Andres Mauricio (2012)
By recourse to the concept of Statistical Complexity we study here the classical-quantum transition in a special system that represents the matter-field interaction. Our work considers two distinct disequilibrium forms based on Euclidean norm and Jensen-Shannon divergence, on the one hand, and analyzes things, on the other one, by using two different numerical approaches for probability distribution, namely, relative wavelet energy and permutation patterns.